The role of functional vitamin D deficiency and low vitamin D reservoirs in relation to cardiovascular health and mortality - Herrmann, Markus; Keppel, Martin H.; Zelzer, Sieglinde; Alonso, Nerea; Cavalier, Etienne; Kleber, Marcus E.; Enko, Dietmar; Scharnagl, Hubert; Pilz, Stefan; März, Winfried (Clinical chemistry and laboratory medicine, 2024)
Objectives: The role of vitamin D deficiency in cardiovascular disease (CVD) is controversial. Inherent biological and analytical limitations compromise the specificity of widely used 25-hydroxyvitamin D [25(OH)D] cut-offs. Simultaneous determination of 25(OH)D and 24,25-dihydroxyvitamin D [24,25(OH) 2 D] permits a functional assessment of vitamin D metabolism. The present study compared the associations of functional vitamin D deficiency and low vitamin D reservoirs with CVD mortality and CVD burden. Methods: 25(OH)D, 24,25(OH) 2 D, the degree of coronary obstruction on angiography, high-sensitive cardiac troponin T (hs-cTnT), N-terminal brain natriuretic peptide (NT-proBNP), and 10-year CVD mortality were obtained from 2,456 participants of the LURIC (Ludwigshafen Risk and Cardiovascular Health) study. Results: Neither low 25(OH)D concentrations nor functional vitamin D deficiency were associated with the number of atherosclerotic coronary arteries or the degree of coronary obstruction. Over a median follow-up of 9.9 years, 454 participants died (23.6%) due to CVD. CVD mortality was doubled in individuals with 25(OH)D concentrations below the widely used cut-off for deficiency of <50nmol/L [20ng/mL] (21.6 vs. 11.5%). In individuals with and without functional vitamin D deficiency, CVD mortality was 25.0 and 16.7%, respectively. NT-proBNP and heart failure prevalence were also higher in vitamin D deficient individuals. Conclusions: Vitamin D deficient individuals have markedly higher CVD mortality, but only marginally higher hs-cTnT concentrations. A higher prevalence of heart failure and higher NT-proBNP concentrations suggest a link between vitamin D deficiency and cardiac function. The traditional and metabolic assessment of vitamin D status showed comparable associations for the different parameters of cardiac health.
Gesehen am 25.11.2024